Development Level Analysis of the Settlements and Micro Regions of the Hungarian-Ukrainian Borderland - Pásztor, Szabolcs (Acta Agraria Debreceniensis, 2012)
This paper aims to make a settlement and micro region-level analysis in case of one of Hungary’s most backwater regions, the Hungarian-Ukrainian borderland. After a brief methodological and theoretical review, it creates a complex development indicator with the help of certain ratios belonging to appropriate groups. It analyzes the exceptionally heterogeneous settlement-level values with applied statistics methods and tries to determine the role of population, population density, the distance from the nearest border-crossing point and the travel time from the centre of the micro region and the county. As its main findings the followings can be mentioned: there are significant development level differences in case of the „periphery of the periphery” micro regions which depend on the number of population, population density and the travel time from the centre of the micro regions.